Iodide-substitution-induced phase transition of chemical-vapor-deposited MoS2. Issue 5 (17th January 2022) - Zhang, Tianfu; Zeng, Zimeng; Xiao, Xiaoyang; Huang, Zhongzheng; Zhao, Jie; Zhao, Yuxin; Jin, Yuanhao; Wang, Jiaping; Fan, Shoushan; Li, Qunqing
Abstract : Molybdenum disulfide (MoS2 ) based electronic devices, particularly field effect transistors, have outstanding performance. Abstract : Molybdenum disulfide (MoS2 )-based electronic devices, particularly field effect transistors, have outstanding performance. However, a large contact resistance between electrode metals and MoS2 limits the full potential of these devices. Here we report an effective, rapid, and convenient approach to inducing phase transitions of MoS2 via treatment with a potassium iodide (KI) solution during device fabrication. The transition from the 2H to the 1T phase in monolayer MoS2 was confirmed using Raman spectroscopy and transmission electron microscope imaging. In electrical transport measurements of the MoS2 transistors subjected to the phase-transition treatment, the normalized on-state current was nearly 50 times greater than that of an untreated transistor. The treatment also resulted in a greater on–off ratio, better output characteristics and a significantly lower contact resistance owing to the phase transition of MoS2 . Hence, we report a new method for inducing a phase transition of MoS2 and provide a reasonable mechanism for this phase transition, offering a new and efficient approach to improved MoS2 devices.